2017
DOI: 10.2495/cmem-v5-n1-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Assessment for Prostheses: State-of-the-Art Review

Abstract: Hundreds of young people have had limbs amputated after being wounded by civil wars, explosions or gunshots. Heat and perspiration within a prosthetic socket are the most common side effects of reduced quality life for prosthesis. Besides, the environment between liner and skin is an ideal host of residual limb skin problems such as contact dermatitis and bacterial infections. It is important to minimize the limiting heat transfer to improve amputee safety and comfort. Usually, when there is a skin problem, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The results showed that the power of the system ranges from 2.1 to 7.0 W at an air temperature of 23°C. Cooling systems for prostheses have been explored previously by Ridha and Ezzat 10 and Abbood et al 11 Cooling systems based on thermoelectric devices were used, where the required parts were cooled based on the value of the supplied electrical energy. [12][13][14][15][16] This method suffers from the problem of storing electricity in relatively heavy batteries, in addition to the low thermal performance coefficient of the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the power of the system ranges from 2.1 to 7.0 W at an air temperature of 23°C. Cooling systems for prostheses have been explored previously by Ridha and Ezzat 10 and Abbood et al 11 Cooling systems based on thermoelectric devices were used, where the required parts were cooled based on the value of the supplied electrical energy. [12][13][14][15][16] This method suffers from the problem of storing electricity in relatively heavy batteries, in addition to the low thermal performance coefficient of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the power of the system ranges from 2.1 to 7.0 W at an air temperature of 23°C. Cooling systems for prostheses have been explored previously by Ridha and Ezzat 10 and Abbood et al 11 …”
Section: Introductionmentioning
confidence: 99%
“…The boundary condition on u implies a tight fit of the prosthetic as no displacement occurs at the boundary. Since sockets are usually made of insulating materials [1], a Neumann boundary condition should be used. However, thermal comfort is desirable and cooling of the socket should be provided [29] in order to maintain a constant temperature, which also indicates that a Dirichlet condition can be used.…”
Section: Introductionmentioning
confidence: 99%